Development Trends of Digital Transformation in Entrepreneurship and Innovation: A Bibliometric Analysis - Utomo, Prio; Cham, Tat-Huei (Journal The Winners, 2023)
The research provided a bibliometric analysis of 340 studies conducted between 2011 and 2022 related to digital transformation in entrepreneurship and innovation. The bibliographic data were extracted from the Scopus database and analyzed using bibliometric tools in R software. The research revealed research trends such as publication and citation per year, top sources, top authors, top documents, and top countries, as well as their impacts. The conceptual structure was analyzed using Multiple Correspondence Analysis (MCA) and hierarchical clustering analysis, which resulted in four cluster keywords related to leadership, entrepreneurial agility, technology impact, digital ecosystems, and digital services. The thematic map analysis identified twenty-seven clusters, which were mapped into four quadrants. Three of those clusters were identified as motor themes (micro foundation, digital global value chain, and digital servitization) which were analyzed in detail through content analysis. The theoretical contribution of the research is to enhance the understanding of how digital technology changes the broad assumptions on the sources, processes, and outcomes of entrepreneurial activities and innovation processes, while the practical contribution provides various contexts of technological impact.